TAFSIR AL-QUR’AN DI MEDSOS: Nadirsyah Hosen’s Resistance to the Politicization of the Quran in Indonesian Social Media - Juwantara, Ridho Agung; Aini, Rezki Putri Nur; Zahra, Dwi Noviatul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
This article aims to examine a book of Nadirsyah Hosen, an Indonesian diaspora in Australia, entitled Tafsir Al-Qur'an di Medsos. Hosen’s interpretation of the Quran is interesting because it is directly related to the actual political context in Indonesia. This study uses a descriptive analysis approach, making the book Tafsir Al-Qur'an di Medsos as the primary source and a number of other books, journals and credible news portals as the secondary sources. By taking five examples of Hosen’s interpretation, namely religious freedom, non-Muslim leadership, the terminology of kâfir, the KPU (Komisi Pemilihan Umum) verse, and the caliphate issue, this study finds that Hosen’s interpretation is a form of resistance to the dynamics and phenomena of contemporary Muslim diversity, especially in the Indonesian context. He interpreted the Quran in respose to the politicization of the scripture through social media platforms, especially in relation to the political situation in Indonesia. He attempts to advocate the relience on credible literature when doing tafsîr and that theverses of the Quran must be understood in a proper context. For example, in addressing the labelling of kâfir and kâfir leadership issue, he suggests that one cannot use it as an excuse to not choosing leaders from non-Muslims because Allah does not forbid Muslims to do good to non-Muslims according to al-Mumtaḥanah [60]: 8. He also identifies inaccuracy of accociating al-Nisâ’ [4]: 108 with the KPU, because the occasion of the revelation of the verse indicates the Quranic defense of an innocent Jew who trapped in a conspiracy from a Muslim.